Muslim Marriages: Age, Mehr, and Social Status (The Pakistan Development Review, 1973)
Marriage, the prescribed legal union between a man and a woman, establishing them in new social roles as husband and wife, is one of the most important events in the life of the two individuals concerned. It is also an important event in the life of the community as a whole. In Pakistan, where marriage is nearly universal and family planning is not yet widely practiced, the number of marriages and age at marriage has important consequences for the fertility level of the population. A Muslim marriage in this country is of additional social and economic significance because of the practice of mehr. In Islam, mehr is a sum of money1 which the husband is duty-bound to give to the wife as part of the marriage contract. Although marriage is an important social institution in Pakistan, little systematic research has been done thus far on its patterns. The most important reason behind this has been the lack of adequate data except that in the census, which unfortunately is very limited for the purposes of such a research. It may be mentioned here that until recently marriages were not officially regis¬tered. A beginning was made after the Muslim Marriage Law Ordinance was passed in 1961, requiring Muslim Marriages to be registered with the local Union or Town Committees. Thus from July, 1961 onwards we have records of interesting data which can serve as a good beginning for research.